1996
DOI: 10.1089/thy.1996.6.553
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Clinical Significance of Thyrotropin Receptor mRNA Expression in Orbital Fat and Eye Muscle Tissues from Patients with Thyroid-Associated Ophthalmopathy

Abstract: We have studied the cellular localization of thyrotropin receptor (TSH-R) mRNA in orbital fat and extraocular muscle tissues from patients with thyroid-associated ophthalmopathy (TAO) using Northern blot, reverse transcriptase polymerase chain reaction (RT-PCR), and in situ hybridization, and we correlated the findings with clinical estimates of ophthalmopathy. Although we failed to detect TSH-R mRNA in orbital tissues by Northern blot, TSH-R cDNA was amplified in orbital fat tissue from 13 of 25 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…The TSHr has been shown to be highly expressed in adipocytes in vivo (28). Numerous results from several laboratories now suggest that the TSHr is expressed in various human extrathyroidal tissues (29,30,31). The presence of the TSHr in human orbital tissue and orbital fibroblasts was demonstrated by using RT-PCR in 1993 (8,9), but the possibility of an illegitimate transcription was raised (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The TSHr has been shown to be highly expressed in adipocytes in vivo (28). Numerous results from several laboratories now suggest that the TSHr is expressed in various human extrathyroidal tissues (29,30,31). The presence of the TSHr in human orbital tissue and orbital fibroblasts was demonstrated by using RT-PCR in 1993 (8,9), but the possibility of an illegitimate transcription was raised (32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Because this receptor is considered a candidate antigen involved in the extrathyroidal manifestations of Graves' disease, its presence has been sought in human orbital and skin tis¬ sues (1). Both full-length TSHR mRNA and a 1.3-kb vari¬ ant TSHR transcript have been detected in normal and Graves' orbital connective tissues using reverse-transcriptase polymerase chain reaction (RT-PCR) (2)(3)(4)(5)(6)(7), and thy¬ rotropin (TSH)-like immunoreactivity has been reported in these tissues (8,9). In addition, two recent studies have demonstrated TSHR mRNA in normal thymus using Northern blotting or RT-PCR (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…These effects can induce thyroid autoimmunity, and recent data have suggested that both the immune-mediated and direct thyroid-toxic effects of IFN play a role in its etiology (38). Our previous study found that the expression of thyrotropin receptor (TSH-R) mRNA in orbital fat tissue from patients with Graves' ophthalmopathy significantly correlated with orbital fat volume and the severity of ophthalmopathy (40). These results suggest that the expression of TSH-R in the orbit may play a role in the pathogenesis and clinical manifestations of ophthalmopathy.…”
Section: Discussionmentioning
confidence: 99%